DETERMINING THE CUTTING RESISTANCE OF MUNG BEAN ROOT - Astanakulov Komil; Turdibekov Ilkhomjon (American Journal of Applied Science and Technology, 2024)
In this article, the shearing resistance of the arrowroot, which is one of the main parameters for harvesting mung bean crops grown on irrigated land, was studied.